Shadow of night - Harkness, Deborah, 1965- (Harkness, Deborah E., 1965- All souls trilogy, 2012)
A follow-up to the best-selling A Discovery of Witches finds Oxford scholar and reluctant witch Diana and vampire geneticist Matthew Clairmont in Elizabethan London, where Diana seeks a magical tutor and Matthew confronts elements from his past at the same time the mystery of Ashmole 782 deepens.